2018
DOI: 10.1007/s10877-018-0118-3
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative measures of EEG for prediction of outcome in cardiac arrest subjects treated with hypothermia: a literature review

Abstract: Cardiac arrest (CA) is the leading cause of death and disability in the United States. Early and accurate prediction of CA outcome can help clinicians and families to make a better-informed decision for the patient's healthcare. Studies have shown that electroencephalography (EEG) may assist in early prognosis of CA outcome. However, visual EEG interpretation is subjective, labor-intensive, and requires interpretation by a medical expert, i.e., neurophysiologists. These limiting factors may hinder the applicab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…Otherwise, we only performed a visual analysis of the EEG background and nor quantitative analysis using machine learning. As visual EEG interpretation could be subjective and requires medical expertise, quantitative EEG analysis could be a promising alternative to visual analysis [29,30]. As our study was designed to evaluate the amplitudes SSEP prognostic value and not specifically the EEG performance, we only compared SSEP prognostic performance to markers of neuro-prognostication already use in the ERC/ESICM guidelines [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Otherwise, we only performed a visual analysis of the EEG background and nor quantitative analysis using machine learning. As visual EEG interpretation could be subjective and requires medical expertise, quantitative EEG analysis could be a promising alternative to visual analysis [29,30]. As our study was designed to evaluate the amplitudes SSEP prognostic value and not specifically the EEG performance, we only compared SSEP prognostic performance to markers of neuro-prognostication already use in the ERC/ESICM guidelines [2].…”
Section: Discussionmentioning
confidence: 99%
“…Lowering the N20-baseline 3). Regarding the second SSEP component i.e N20-P25, an amplitude > 3.2 µV predicted good outcome with a specificity of 93 [90-96]% and sensitivity of 29 [23][24][25][26][27][28][29][30][31][32][33][34]%, although a threshold of 4 µV increased specificity (sp = 95 [92-97] %) but decreased sensitivity (se = 14 [10-18]%) (Table 3). The combination of N20-baseline > 2 µV with a benign EEG presented a higher specificity (sp = 96.9 [95-99]%) with a similar sensitivity (se = 33.3 [28-39]%) although combination of N20-P25 with benign EEG was also highly specific (sp = 97 [93-98]%) but poorly sensitive (se = 17 [13-21]%).…”
Section: Prediction Of Good Outcomementioning
confidence: 99%
“…Considering that visual analysis remains subjective, quantitative analyses of the EEG signals (qEEG) using machine learning have been recently developed [89]. These qEEG modalities may be broadly categorized into spectral and connectivity analyses [90].…”
Section: Eeg Quantitative Analysesmentioning
confidence: 99%
“…Finally, the spectrogram is obtained. Studies have shown that QEEG has achieved good results in the evaluation of neurocognitive function in patients with Parkinson's and Alzheimer's [ 7 ]. Montreal cognitive assessment (MoCA) is a cognitive assessment tool widely used in clinical practice worldwide.…”
Section: Introductionmentioning
confidence: 99%